DIFFERENCES IN THE NUMBER OF LEUKOCYTES WITH STRENUOUS PHYSICAL ACTIVITY AND WITHOUT PHYSICAL ACTIVITY - Silviani, Ana; Kurniawan, Aziyo; Bastian, Bastian; Sari , Indah (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction – Physical fitness is the body's ability to carry out physical activities, a person will get good fitness for physical sports activities.Physical fitness consists of several components, namely respiratory endurane carido,muscle endurance,muscle speed, and flexibility.Physical activity's movement.Muscles of the body and their support systems consisting of light,moderate, and strenuous physical activity.Strenuous physical activity will result in a lot of sweat with a counted heart rate>145 beats/minute.The effect of exercise on changes in immunity can be seen through changes in the number of leukocytes.. Purpose – This study to determine whether there are differences of leukocytes with heavy physical activity and without activity. Methodology – The type of research used comparative Cross-sectional at Hematology Laboratory of IKesT Muhammadiyah Palembang. Samples were taken from 30 respondents with the inclusion criteria.The results were processed using the Statistical Product and Service Solution (SPSS) program.Research data on differences of leucocytes with heavy physical activity and without activity by the dependent t test. Findings – The average number of leucocytes with heavy physical activity was 8.66 thousand/mm3,while the average without activity was 7.98 thousand/mm3.The results by dependent T Test show that the significant value’s p=0.000.The p value obtained is p<0.05,Can be concluded that there's an effect of leukocytes with strenuous physical activity and no activity. Based on the results of study can be concluded,there are differences of leukocytes with physical activity and without activity. Originality – This study used 30 blood samples to determine the difference of leukocytes with strenuous physical activity and without activity by Dependent T test